Digital Literacy Socialization for Health Workers in Simeulue Regency - Muzammil, Abdul; Adib, Adib; Azwanda, Azwanda; Masykur, Masykur; Jayadi, Farid; Ridha, Arrazy Elba; Hadi, Fajri (Universitas Syiah Kuala, 2024)
This community service activity aims to enhance health workers' understanding of digital literacy and community empowerment techniques by utilizing digital access, thereby supporting more effective public health literacy. The activity was conducted at two health centers in Simeulue Regency, namely Teupah Selatan Health Center and Teupah Barat Health Center, on June 17, 2024, from 09:00 to 13:00 WIB, with a total of 44 participants. The method used in this activity involved adapting the Lasswell communication process, where information was conveyed by resource persons and health promotion officers to health workers offline. The activity was considered successful due to the enthusiasm shown by the participants. The evaluation results indicate an improvement in the participants' knowledge and skills, as well as a positive impact on their understanding of digital literacy